Islamic Theological Thought of Muhammad Zain al-'Asyi in the Bidayah al-Hidayah - Harpandi Dahri (Islamic Thought Review, 2023)
The rapid development of science in the archipelago, especially in Aceh, is characterized by the emergence of manuscripts in various fields of study. Apart from the big names that have been very well-known, such as Hamzah Fansuri, Syamsuddin As-Sumatrani, and Nuruddin Ar-Raniri, many other names are also very productive. One of the thinkers who has not been widely studied in the Aceh thought tradition is Muhammad Zain al-Asyi, who has many works in various fields such as Sufism, fiqh, monotheism, history, and others. This article aimed at analyzing the manuscript of Bidayah al-Hidayah, a work of Muhammad Zain al-Asyi related to Islamic theological thought. This study used philological methods in addition to content analysis. This work contains the ideology of wujudiyyah developed by its predecessors, namely Hamzah Fansuri and Syams Al-Din al-Sumatrani. Apart from these teachings, it was also found that al-Asyi developed the instructions of the Sunni aqidah of Abu Hasan al-Asy'ary and Abu Mansur al-Maturidi written by al-Imam al-Sanusi in Matn Umm al-Barahin.